The Aeneid - Virgil (University of Chicago Press, 2017)
Contents – Preface – A Note on Meter – A Note on the Translation – Book One – Book Two – Book Three – Book Four – Book Five – Book Six – Book Seven – Book Eight – Book Nine – Book Ten – Book Eleven – Book Twelve – Acknowledgments.
Keywords: Epic poetry; Latin–Translations into English